Способ получения микрокристаллов нитрида алюминия - Ильин А. П. Александр Петрович; Мостовщиков А. В. Андрей Владимирович; Коршунов А. В. Андрей Владимирович; Толбанова Л. О. Людмила Олеговна
опубл. 27.12.11